Training on Strategies to Pass CPNS Test for CPNS Applicants Through the Giat Belajar Abadi Platform - Santoso, Eka Krisna; Azka, Muhammad; Kamila, Isti; Indrawan; Rauf, Nurul Maqfirah; Bahar, Nur Qadri (Jurnal Pengabdian Masyarakat Inovatif, 2024)
The acceptance of Civil Servant Candidates (CPNS) is an opportunity highly anticipated by the community to build a career in the government sector. However, tight competition and complex selection stages are often the main challenges for applicants. Many applicants fail due to a lack of understanding of the selection process, ineffective learning strategies, and minimal information about the success criteria. The partner of this Community Service activity is Giat Belajar Abadi. Giat Belajar Abadi (GBA) is a lifelong learning platform designed to help people improve their skills and expand their knowledge. This platform offers a variety of classes and learning programs related to business, self-development, and more. However, Giat Belajar Abadi has not yet opened a class for training strategies to pass the Civil Servant Candidate (CPNS) test. Therefore, a community service program is needed for Giat Belajar Abadi partners by opening a training class on CPNS test strategies. This class will help CPNS applicants to be better prepared for the selection, both technically and mentally, increasing their chances of success. The purpose of this Community Service activity is to increase understanding of CPNS selection strategies through Giat Belajar Abadi partners. Therefore, the target audience of this activity is CPNS applicants. The outcome of this Community Service program is an increased understanding of CPNS selection strategies. Through this program, it is hoped that the success rate of participants in the CPNS selection will increase, while creating more competent human resources ready to contribute to the government sector. This program also has a long-term impact on improving the quality of CPNS applicants’ preparation in the future.